In vitro evaluation of pyridine-2-azo-p-dimethylaniline cephalosporin, a new diagnostic chromogenic reagent, and comparison with nitrocefin, cephacetrile, and other beta-lactam compounds. - Jones, R N (1982)
Pyridine-2-azo-p-dimethylanaline cephalosporin (PADAC), a chromogenic reagent which is purple and changes to yellow upon cleavage of its beta-lactam ring, was evaluated in comparison with other chromogenic cephalosporins. PADAC exhibited little antimicrobial activity against gram-negative bacteria, but did have good activity (minimum inhibitory concentration, 0.12 to 0.5 microgram/ml) against Staphylococcus aureus, a quality comparable to nitrocefin. Nitrocefin, however, demonstrated an unexpected and uniquely potent activity against Streptococcus faecalis (minimum inhibitory concentration, less than or equal to 0.06 to 0.12 microgram/ml) The relative hydrolysis rate of PADAC when subjected to six different beta-lactamases was substantially greater than that of cephacetrile, but less than that of nitrocefin. The relative hydrolysis rates of PADAC and nitrocefin were comparable with type IIIa beta lactamase and the derived from Bacillus cereus. The inhibition of beta-lactamase hydrolysis of the chromogenic cephalosporin substrates by six enzyme-stable inhibitors was generally greater with PADAC than with nitrocefin. Unlike nitrocefin, PADAC mixed with 50% human serum or various broth culture media showed no evidence of color change or degradation over several hours. The subsequent enzyme hydrolysis rates of such mixtures were the same as in phosphate buffer. Beta-lactamase-containing bacterial suspensions and clinical specimens containing such bacteria produced positive visual and spectrophotometric color changes when mixed with PADAC or nitrocefin. Although color changes occurred more slowly with PADAC than with nitrocefin, PADAC was not adversely influenced (non-enzyme-related color change) by the protein content of specimens. PADAC appears to be a promising alternative for beta-lactamase diagnostic testing in the clinical and research microbiology laboratory.